2015
DOI: 10.1590/1980-57642015dn92000014
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune limbic encephalitis: A manifestation of systemic lupus erythematosus in the central nervous system

Abstract: Autoimmune limbic encephalitis (ALE) associated with systemic lupus erythematosus (SLE) is a rare entity with few reports in the literature to date. In general, ALE associated with SLE has a satisfactory response to immunosuppressive treatment (RIT), but the pathogenesis of this association is poorly understood and may include an autoimmunity component. We report a case study describing the diagnosis and management of limbic encephalitis in a patient with active Systemic Lupus Erythematosus disease (SLE) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…In most cases, patients had a confirmed history of SLE before experiencing encephalitis symptoms (Angst et al, 2015;Asmaa et al, 2022;Kelley et al, 2018;Li et al, 2022;Raventhiranathan et al, 2022;Selcuk et al, 2011;Stubgen et al, 1998;Sugi et al, 2018;Tsuchiya et al, 2021;Zhang et al, 2021). The time interval between the initial SLE diagnosis and the onset of neurological complications varied from two weeks to 14 years (Angst et al, 2015;Asmaa et al, 2022;Kelley et al, 2018;Li et al, 2022;Selcuk et al, 2011;Stubgen et al, 1998;Zhang et al, 2021). However, four cases initially showed neuropsychiatric symptoms.…”
Section: Initial Encephalitis and Sle-related Presentationmentioning
confidence: 99%
“…In most cases, patients had a confirmed history of SLE before experiencing encephalitis symptoms (Angst et al, 2015;Asmaa et al, 2022;Kelley et al, 2018;Li et al, 2022;Raventhiranathan et al, 2022;Selcuk et al, 2011;Stubgen et al, 1998;Sugi et al, 2018;Tsuchiya et al, 2021;Zhang et al, 2021). The time interval between the initial SLE diagnosis and the onset of neurological complications varied from two weeks to 14 years (Angst et al, 2015;Asmaa et al, 2022;Kelley et al, 2018;Li et al, 2022;Selcuk et al, 2011;Stubgen et al, 1998;Zhang et al, 2021). However, four cases initially showed neuropsychiatric symptoms.…”
Section: Initial Encephalitis and Sle-related Presentationmentioning
confidence: 99%
“…Autoimmune antibody-mediated encephalitis (Fig 17) is rare, but the incidence of this condition in SLE may be underestimated. One study (44) showed antibody-mediated inflammation of the striatum in 7% (44,63) of patients with NPSLE, with associated hippocampal lesions (Figs 18, 19) (44,63,64). The mechanism is unclear but is believed to be related to breached neuroimmune interfaces in the BBB and choroid plexus, with invasion by anti-NMDAR, aPL, or anti-Rib-P antibodies resulting in neuronal excitotoxicity.…”
Section: Autoimmune Antibody-mediated Encephalitismentioning
confidence: 99%
“…Šiuo konkrečiu atveju autoimunitetas buvo svarbiausias veiksnys, susijęs su ALE. Stebėtas geras atsakas į imunoterapiją [34]. 34 metų moteriai, sergančiai SRV, pasireiškė bendras nuovargis, traukuliai, atminties praradimas.…”
Section: Literatūros Apžvalga Ir Diskusijaunclassified